In -vitro evaluation of mung bean (Vigna radiata L., Wilczek) genotypes for drought tolerance and productivity - Ganta, Tekle Yoseph; Mekbib, Firew; Amsalu, Berhanu; Tadele, Zerihun (Journal of Agriculture and Environmental Sciences, 2022)
Drought stress is the most important factor that limits mung bean production and productivity at large in drought-prone areas of Ethiopia. It is hence necessary to identify and verify drought-tolerant and productive varieties of major crops grown in drought areas of the country like mung bean. The present study was conducted to evaluate mung bean genotypes for drought tolerance under in-vitro conditions and to assess the performance of the in-vitro developed regenerants under greenhouse conditions. The in-vitro experiment was thus arranged in a factorial experiment using a completely randomized design with three replications. Three mung bean genotypes, NLLP-MGC-06/G6 (tolerant), VC6368 (46-40-4)/G34 (moderate), and NLLP-MGC-02/G2 (sensitive) and five polyethylene glycol (PEG) levels (0, 0.5, 1.0, 1.5, and 2.0%) were used. The analysis of variance exhibited significant differences among the genotypes for all the studied parameters except the number of roots per shoot. There were significant differences observed among PEG levels for all the studied parameters. Significant genotypes x PEG interactions were observed for all the studied traits except total roots per culture and survival percentage. Increasing polyethylene glycol concentration from 0% to 2.0% in the medium caused a gradual increase in root length from 0.49 cm at 0% PEG to 1.17 cm at 2.0% PEG, respectively. This revealed an adaptive mechanism to the decreased moisture content in the root zones of plants and enhanced increased root length to reach deeper water in the soil. Regenerant from the treatment combinations of G34 (0) exhibited the highest values for the number of primary branches per plant (4.00). Grain yield for the in-vitro regenerated plants evaluated at greenhouse conditions ranged from 552.52 kg ha-1 at the treatment combination of G2 (1) to 996.23 kg ha-1 at the treatment combinations of G6 (0). Most of the regenerants obtained from NLLP-MGC-06/G6 and VC6368 (46-40-4)/G34 showed the best performance under the greenhouse for drought-tolerance under the in-vitro condition, suggesting that the accumulated performance of the tested regenerants under in-vitro conditions was realized under greenhouse conditions. It also indicated that in-vitro culture is an important tool to identify and verify drought-tolerant genotypes and improve desirable agronomical traits. Further study is indeed required to understand the mechanism of drought tolerance for in-vitro-selected somaclones.